2023
DOI: 10.1002/nop2.1597
|View full text |Cite
|
Sign up to set email alerts
|

Integrated factors affecting intention of COVID‐19 preventive behaviours including vaccination in Korea

Abstract: Aim The aim of the study was to determine the multiple potential contributing factors in preventive behaviours, including COVID‐19 vaccination for an effective campaign strategy. Design This is a descriptive correlation study to examine the effects of the behavioural outcome, attitude, subjective norm, perceived behavioural control, optimistic bias and social stigma on the intention of preventive behaviour, based on Ajen's Theory of Planned Behaviour. Methods The survey was performed by a professional research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This result demonstrates how challenging it is to isolate oneself from community life and take preventive actions perceived as inevitable The previous finding 9 proved that the impact on others of not performing preventive measures influences an individual’s willingness to take preventive action. Nonetheless, another study 36 ascertained that social groups are influenced by our society and what others think affect in decision-making when it comes to engaging in preventive behavior. In either circumstance, it highlights the influence of others on an individual’s decision to comply preventive action.In addition, results 35 indicated that information seeking influences preventive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This result demonstrates how challenging it is to isolate oneself from community life and take preventive actions perceived as inevitable The previous finding 9 proved that the impact on others of not performing preventive measures influences an individual’s willingness to take preventive action. Nonetheless, another study 36 ascertained that social groups are influenced by our society and what others think affect in decision-making when it comes to engaging in preventive behavior. In either circumstance, it highlights the influence of others on an individual’s decision to comply preventive action.In addition, results 35 indicated that information seeking influences preventive behavior.…”
Section: Discussionmentioning
confidence: 99%